2021
DOI: 10.1038/s41598-021-88016-x
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of biogenic zinc oxide nanoparticles to soil organic matter cycling and their interaction with rice-straw derived biochar

Abstract: Given the rapidly increasing use of metal oxide nanoparticles in agriculture as well as their inadvertent addition through sewage sludge application to soils, it is imperative to assess their possible toxic effects on soil functions that are vital for healthy crop production. In this regard, we designed a lab study to investigate the potential toxicity of one of the most produced nanoparticles, i.e. zinc oxide nanoparticles (nZnO), in a calcareous soil. Microcosms of 80 g of dry-equivalent fresh soils were inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…The reductions observed in C min value can be related to a lower decomposer community in the presence of ZnO-NPs as previous studies have indicated that the decomposer microbial community is signi cantly vulnerable to ZnO-NPs(Collins et al, 2012;Ge et al, 2011;Shah et al, 2022). This nding is in agreement with that ofShemawar et al (2021), indicating that leaf litter C mineralization was decreased after ZnO-NPs addition to mesocosms containing sandy soil. García-Gómez et al (2015) also showed a substantial decline in the C mineralization of glucose in soils treated with ZnO-NPs.…”
supporting
confidence: 86%
See 1 more Smart Citation
“…The reductions observed in C min value can be related to a lower decomposer community in the presence of ZnO-NPs as previous studies have indicated that the decomposer microbial community is signi cantly vulnerable to ZnO-NPs(Collins et al, 2012;Ge et al, 2011;Shah et al, 2022). This nding is in agreement with that ofShemawar et al (2021), indicating that leaf litter C mineralization was decreased after ZnO-NPs addition to mesocosms containing sandy soil. García-Gómez et al (2015) also showed a substantial decline in the C mineralization of glucose in soils treated with ZnO-NPs.…”
supporting
confidence: 86%
“…The presence of NPs in the soil can signi cantly in uence the ability of the soil microorganisms to mineralize organic substances, and therefore a measurement of soil respiration kinetics is a valuable method to assess the impacts of NPs on soil microbial activity (Shemawar et al, 2021;Xin et al, 2020). In this study, the time-dependent organic C mineralization data were tted by the rst-order, double rst-order, rst-order E, and special models.…”
Section: Effects Of Zno-nps On Carbon Mineralization Kineticsmentioning
confidence: 99%
“…Biochar is rich in a range of mineral nutrients including nitrogen, phosphorus, potassium, calcium, magnesium, zinc, etc., depending upon the feedstock type and pyrolysis temperature [113]. Upon addition to soil, it is decomposed gradually to release these nutrients in the soil solution [114][115][116].…”
Section: Mechanistic Understanding Of Interaction Of Pgpr and Biocharmentioning
confidence: 99%
“…This approach of utilising the ZnO –SOM interaction interface may offer the required advantage of nutrient use efficiency due to its solubility-driven slow release moderated further by carbon sequestration. Thus, collectively leading to sustainable agriculture for a climate-resilient future 15 17 .…”
Section: Introductionmentioning
confidence: 99%